Geopolitics of Nigeria: A Politically Divided but Socially Connected Country - Muhammad Abdullahi Maigari; Dikko Umaru Radda; Ibrahim Arafat (PT Pro Panoramic Solution, 2026)
Nigeria is among the world's most ethnically divided countries, with more than 250 ethnolinguistic groups coexisting. The objectives of this paper are to examine the influence of domestic borders on Nigerians. It also analyzes how the country has remained undivided despite the existence of colonial, post-colonial, and political borders. The researchers approached this problem by collecting secondary data from documented sources and analyzing it using content analysis. The study found that Resource allocation, political appointments, and electoral contests are among the considerations, along with religion and ethnic affiliations. On the surface, geopolitical and ethnoreligious factors are blown out of proportion in Nigeria, where some citizens politicize almost all government policies, programs, and projects. Despite overt political boundaries created and institutionalized by those in government, beneath the surface, citizens interact without considering such demarcations. People carry out their routine financial transactions with customers from different regions of the country without considering geopolitical and ethnoreligious divisions, which aligns with the constructivist theory of border studies. Therefore, this article concludes that politicians create tangible boundaries to realize their political motives. Still, ordinary citizens, in their daily interactions with people from different political divides, move across those boundaries without knowing they exist.